Carbon dioxide absorption in aqueous ammonia using pilot scale packed column - Fong, See Heng (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
The absorption of CO2 in different liquid absorption has been studied by overall gas absorption (f) in a randomly pilot scale gas absorption column. The most effective ways to absorb the gas CO2 into the solvent such as ammonia was using chemical solvent absorption method to reduce the emission of CO2 into the environment. However, the research was carried out through the laboratory-oriented and conduct with the pilot scale of gas absorption column and measurement equipment. The mechanism of the gas absorption column was using counter current absorption which means that the liquid would flow from top to the bottom of gas absorption column meanwhile the gas would flow from bottom to the top of the gas absorption column. The gas absorption would appear when the gases were interacting with the solute of liquid solvent. The gas flow rate and liquid flow rate would manipulate the response of overall gas absorption which indicated that the rate of the CO2 gas absorbed into solvent. From the experimental result, it was found that the overall absorption rate was increased as the gas flow rate increased; the result also shows that the overall absorption rate of CO2 increased as liquid flow rate increased. In general, a higher CO2 capture was obtained at a liquid flow rate of 0.5 GPM with gas flow rate of 2.0 LPM where the solvent that used was 0.01 mole of ammonia. This conditions shows that it was the optimum condition of CO2 absorption into the aqueous ammonia.